Supply Chain and Logistics Management and an Open Door Policy Concerning Cyber Security Introduction - Burrell, Darrell Norman; Bhargava, Nimisha; Bradley-Swanson, Orna; Harmon, Maurice; Wright, Jorja; Springs, Delores; Dawson, Maurice (International Journal of Management and Sustainability, 2020)
The need for integrity and reliability in the supply chain and logistics management operations has a well-established array of theoretical frameworks that guide organizations and managers in the field. However, what is missing is a comprehensive, established framework for logistics and supply chain cybersecurity. The emerging area of cyber-supply chain security continues to lack suitable models to help secure critical data and systems. In all industries and fields today, cybersecurity is no longer just an information technology issue. It is a business sustainability and business strategy issue. The human factors in the cyber-supply chain operations represent the actions or events when human error results in a successful hack or data breach. Today, protecting logistics and supply chain organizations from cyber and data security risks is no longer just an information technology employee function. Every organizational employee has a responsibility in the data protection process. Progressive organizations are ones that can create methods, policies, and approaches that encourage employees to play an active role in the information and cybersecurity process. This paper explores innovative approaches around open-door systems as a proactive data security and cybersecurity risk reduction organizational strategy. This research provides cyber-supply chain practitioners and scholars an array of concepts to help them understand and describe the dynamics of cyber-supply chain and logistics management data security vulnerabilities and opportunities for process improvements.